Study on Experience Differentiation Strategy (1): Concepts of Customer Experiences - Shin’ya Nagasawa (Modern Perspectives in Economics, Business and Management Vol. 4, 2021)
In a mature market like the Japanese economy, “experiential marketing” has received attention as a “differentiation strategy.” In this study, we investigate the concepts of experiential marketing. The results show that 1) experiences are involved in obtaining, consuming, and disposing of products, 2) experiences occur in situations consumers face, and 3) experiences are behaviors and physiological/psychological effects. This understanding of experiences helps us effectively use experience as a differentiation strategy. This study proposes a novel definition and provides methodologies for customer experience and strategies. Further exploration of successful products or service examples should be addressed in the future.